PENGARUH DUKUNGAN ORANG TUA DAN GENDER TERHADAP MOTIVASI BELAJAR SISWA KELAS IX SMP PGRI 8 DENPASAR - Sunyata, Dion Putra; Ida Ayu Karina Adityanti Manuaba; I Gusti Agung Ayu Yunita Utami (Journal of Innovation Research and Knowledge, 2026)
This study examined the extent to which parental support and gender influences the learning motivation of Grade IX students at SMP PGRI 8 Denpasar. The background of this research is that students learning motivation often becomes a complex issue influenced by various internal and external factors, including parental support and gender differences that shape how students engage in learning activities. Adopting a quantitative associative design, data were obtained from 100 students (51 girls, 49 boys) using two Likert-type instruments. Both measures satisfied reliability and validity requirements. After the assumptions of normality, linearity, and multicollinearity were met, multiple-linear regression in JASP showed that the overall model was significant (F < 0.001; R² = .25). Parental support emerged as the strongest predictor (β = 0.597, b = 0.382, p < 0.001), while gender also contributed significantly (β = 0.268, b = 5.401, p = 0.003), indicating that girls reported higher motivation than boys at comparable support levels. Follow-up simple regressions revealed that parental support explained 21% of the variance in intrinsic motivation and 52% in extrinsic motivation. The findings highlight the importance of meaningful parental involvement and gender-responsive strategies for enhancing students learning motivation.